Ecto- and Endoparasites of the Black Bear in Northern Wisconsin - Manville, Albert M. (University of Wisconsin-Stevens Point, College of Natural Resources, 1976)
Black bears (Ursus americanus) were live-trapped and examined for ectoparasites during the summers of 1974 and 1975 in northern Wisconsin. Nine bears were captured in 1974 and 104 bears (including 18 recaptures) were captured in 1975. Thirty-five (79.5%) of 44 captures from Clam Lake in 1975 carried the dog tick (Dermacentor variabilis Say, 1821), one (2.3%) the winter tick (Q. albipictus Packard, 1869), and one (2.3%) the black-legged tick (Ixodes scapularis Say, 1821) -- a new host and state record. Forty-five (75%) of 60 bears captured in Iron County in 1975 carried dog ticks. Dog ticks occurred on 76.9% of the 1975 captures and on 72.6% of all captures. Four (6.7%) of the bears captured in Iron County in 1975 had moderate to heavy infestations of a louse (Trichodectes pinguis euarctidos Hopkins, 1954). Mange was observed on five (5.8%) bears captured in 1975; two Demodex (Owen, 1843) mites were discovered in a scab sample. The black bear is a new recorded host for this mite. None of 70 tissue samples was positive for Demodex. A flea was collected in 1974 from an Iron County bear. Dental caries were present in nine (10.5%) bears captured in 1975. Periodontal disease was present in one (1.2%) Clam Lake bear. Twenty-eight viscera were obtained from hunter-killed bears during the 1974 and 1975 fall bear hunting seasons. Twenty-five (89.3%) intestinal tracts contained ascarid worms (Baylisascaris transfuga Rudolphi, 1819). Fifty-nine (64.1%) of 92 fecal samples examined from live-trapped bears had B. transfuga eggs; 11 (39.3%) of 28 samples examined from viscera were positive. An unidentified hookworm larva was recovered froa a bear captured in 1975. Adult filarial worms (Dirofilaria ursi Yamaguti, 1941) were found in two (7.1%) viscera. Seventeen (19.5%) of 87 blood smears contained microfilariae. The broad fish tapeworm (Diphyllobothrium latum Linnaeus, 1785), reportedly common in humans and black bears in the Lake Superior region earlier in this century, was absent from all viscera and fecal samples examined. The trichina worm (Trichinella spiralis Owen, 1835) was found in 6 (3.8%) of 163 Wisconsin bears in a study from 1970 to 1973; none was found in viscera or tissue samples examined from this study. Tooth sectioning revealed an age range from 0.5 to 15.5 years for bears captured in 1975. The average age for males and females was 4.5 and 6.02 years, respectively.